The dynamic impacts of renewable energy and tourism investments on international tourism: evidence from the G20 countries - Lu, Zhou; Gozgor, Giray; Lau, Chi Keung Marco; Paramati, Sudharshan Reddy (Journal of Business Economics and Management, 2019)
This paper investigates the effects of the renewable energy consumption and the tourism investments along with the per capita gross domestic product (GDP), the real effective exchange rate, and trade openness on both tourism revenues (total tourism contribution to GDP) and international tourist arrivals in the sample of the G20 members. The annual data from 1995 to 2015 and the panel econometric techniques are utilized to achieve the objectives of the current paper. The results for the long-run elasticities from the panel fully modified ordinary least squares (FMOLS) estimations suggest that the renewable energy uses and tourism investments have a considerable positive impact on both the tourism revenues and the tourist arrivals. Given these results, it is argued that promoting both renewable energy and tourism investments should be considered as the major driving forces of tourism development in the G20 countries. Given these arguments, policymakers should initiate more of sustainable tourism development policies, which may assist those countries to expand the tourism industry further.